Developmental refinement of synaptic transmission on micropatterned single layer graphene. (January 2018) - Keshavan, Sandeep; Naskar, Shovan; Diaspro, Alberto; Cancedda, Laura; Dante, Silvia
Graphical abstract: Abstract: Interfacing neurons with graphene, a single atomic layer of sp 2 hybridized C-atoms, is a key paradigm in understanding how to exploit the unique properties of such a two-dimensional system for neural prosthetics and biosensors development. In order to fabricate graphene-based circuitry, a reliable large area patterning method is a requirement. Following a previously developed protocol, we monitored the in vitro neuronal development of geometrically ordered neural network growing onto patterned Single Layer Graphene (SLG) coated with poly-D-lysine. The microscale patterns were fabricated via laser micromachining and consisted of SLG stripes separated by micrometric ablated stripes. A comprehensive analysis of the biointerface was carried out combining the surface characterization of SLG transferred on the glass substrates and Immunohistochemical (IHC) staining of the developing neural network. Neuronal and glial cells proliferation, as well as cell viability, were compared on glass, SLG and SLG-patterned surfaces. Further, we present a comparative developmental study on the efficacy of synaptic transmission on control glass, on transferred SLG, and on the micropatterned SLG substrates by recording miniature post synaptic currents (mPSCs). The mPSC frequencies and amplitudes obtained on SLG-stripes, SLG only and on glass were compared. Our results indicate a very similar developmental trend in the three groups, indicating that both SLG and patterned SLG preserve synaptic efficacy and can be potentially exploited for the fabrication of large area devices for neuron sensing or stimulation. Statement of significance: This paper compares the morphological and functional development of neural networks forming on glass, on Single Layer Graphene (SLG) and on microsized patterned SLG substrates after neuron spontaneous migration. Neurons developing on SLG are viable after two weeks in vitro, and, on SLG, glial cell proliferation is enhanced. The functionality of the neural networks is demonstrated by measuring the development of neuron synapses in the first and second week in vitro. Preserving the neuron synaptic efficacy, both homogeneous and patterned interfaces based on graphene can be potentially exploited for the fabrication of large area devices for neuron sensing or stimulation, as well as for next generation of bio-electronic systems, to be used as brain-interfaces.